2023
DOI: 10.1021/acs.orglett.3c01240
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Aerobic α,β-Dehydrogenation

Abstract: An iron-catalyzed direct aerobic α,β-dehydrogenation of carbonyls has been reported. The combination of tert-butyl nitrite and N-hydroxyphthalimide worked as the organo cocatalyst system; thus, no extra transition metal reagents are required. A large variety of lactams and flavanones as well as lactone and thiochromen-4-one could be produced via this method in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Recently, a FeCl 3 -catalyzed aerobic α,β-dehydrogenation with organo cocatalyst tert-butyl nitrite and N-hydroxyphthalimide (NHPI) have been reported by Kang and Qu. [34] The α,βunsaturated lactones and lactams could be obtained in moderate to high yield under the optimal conditions (Scheme 15), which included steroid-derived substrate and flavanones with heterocyclic substituents. To investigate the reaction mechanism, a series of control experiments were performed.…”
Section: αβ-Dehydrogenation Of Lactonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a FeCl 3 -catalyzed aerobic α,β-dehydrogenation with organo cocatalyst tert-butyl nitrite and N-hydroxyphthalimide (NHPI) have been reported by Kang and Qu. [34] The α,βunsaturated lactones and lactams could be obtained in moderate to high yield under the optimal conditions (Scheme 15), which included steroid-derived substrate and flavanones with heterocyclic substituents. To investigate the reaction mechanism, a series of control experiments were performed.…”
Section: αβ-Dehydrogenation Of Lactonesmentioning
confidence: 99%
“…Lactams are a kind of important structure because they are usually found in biological molecules, which may exist in natural products, agrochemicals and pharmaceuticals. [34,37] Dong and co-workers developed a direct catalytic method to synthesize α,β-unsaturated lactams under mildly acidic conditions (Scheme 19). [37b] This approach is effective for a big range of substrate scope, such as lactams with various functional groups at different position, lactams with different ring size and so on.…”
Section: αβ-Dehydrogenation Of Lactamsmentioning
confidence: 99%
“…Following our work on the Fe-Cl 3 -catalyzed ,-dehydrogenation of carbonyl compounds, in 2023, we reported a FeCl 3 -catalyzed aerobic ,-dehydrogenation with an organo-cocatalyst, tert-butyl nitrite and N-hydroxyphthalimide (NHPI), which effectively solved the problem of the low yields encountered with the ,-unsaturated lactones and lactams in our previous work (Scheme 3). 23 A variety of ,-saturated lactones, lactams and flavanones, including steroid-derived substrates and flavanones with heterocyclic substituents, could be dehydrogenated under the optimized conditions, generating the corresponding products in moderate to good yields. Control experiments indicated that a radical process may be involved, and FeCl 3 as a Lewis acid may activate 23.…”
Section: Scheme 2 Iron-catalyzed -Dehydrogenation Of Carbonyl Compo...mentioning
confidence: 99%
“…For constructing carbon–carbon and carbon–heteroatom bonds in modern organic synthesis, iron, as the most abundant transition metal in the Earth's crust, has found extensive application as an eco-friendly and readily available catalyst. 1–11 Inspired by iron-containing enzyme catalysis, 12,13 the iron-catalyzed C(sp 3 )–H bond oxidation, coupled with the utilization of molecular oxygen, has emerged as a highly promising reaction over the past decade. 14–24 In 2015, Li's group pioneered the utilization of cross-dehydrogenative coupling (CDC) to develop an iron salt-catalyzed cross-dehydrogenative arylation between 3-substituted indolin-2-ones generating a series of 3,3′-disubstituted oxindole compounds.…”
Section: Introductionmentioning
confidence: 99%